A randomized, double-blind, placebo-controlled clinical trial to evaluate pregabalin efficacy in the treatment of behavioral and psychological symptoms of dementia in patients with Alzheimer’s disease - Maleki, Leyla; Mohammadian, Fatemeh; Panahishokouh, Mahsa; Mohebbi, Niayesh (Frontiers in Neuroscience, 2024)
BackgroundBehavioral and Psychological Symptoms of Dementia (BPSD) are common during Alzheimer’s disease and cause severe problems for patients and their caregivers.ObjectivesTo assess the therapeutic efficacy of Pregabalin in comparison with a placebo in treating BPSD in patients with Alzheimer’s disease (AD) visiting the memory and cognition clinic of Roozbeh Psychiatric Hospital in Tehran, Iran.MethodsA 12-week double-blind, randomized comparison of Pregabalin and placebo treatments was conducted in 53 patients with DSM-V diagnosis of dementia of Alzheimer’s type. They were randomly assigned to receive Pregabalin (doses: 50 titrated up to 300 mg/day) or a placebo. Clinical response was evaluated using the Neuropsychiatric Inventory (NPI), and the Behavioral Pathology in AD Rating Scale (BEHAVE-AD) scores compared with baseline. Side effects were also recorded carefully.ResultsPatients receiving Pregabalin had better outcomes in comparison with patients receiving a placebo regarding both NPI and BEHAVE-AD scores after 12 weeks (p-value = 0.009 for NPI and p-value = 0.003 for BEHAVE-AD). There was also a statistically significant decrease in the treatment group depression sub-score regarding NPI and BEHAVE-AD (respectively, p-value =0.000, 0.003). The caregiver burden sub-score of the NPI test was also lower in patients receiving pregabalin (p-value = 0.000). There was no statistically significant difference between the occurrence of adverse effects between the two groups (p-value = 1.00).ConclusionPregabalin at a dose of 300 mg/day was well tolerated and associated with reductions in the severity and frequency of behavioral symptoms in patients with AD. Pregabalin could be considered a favorable choice for treating BPSD in adults with mild to moderate stages of Alzheimer ‘s-type dementia, considering its befitting safety profile.Clinical trial registrationhttps://www.irct.ir/trial/52750, identifier IRCT20201201049553N1